A New Procedure For Reservoir Fluid Characterization With Equation Of State (EOS) - Ego Syahrial (Scientific Contributions Oil and Gas, 2009)
A new procedure for reservoir fluid characterization through equation of state (EOS) is proposed. It is applied in a selecting the most appropriate fluid composition for the purpose of reservoir fluid characterization. A Hoffman-Crump-Hocott plot is used to determine whether or not the streams are genuine equilibrium fluids. With the aid of phase diagram and saturation pressure from RFT, the most appropriate fluid sample was chosen for fitting an equation of state to experimental data through regression. Based on data analysis and quality control of all PVT data suggested that fluid from UP-1 DST-3 is the best representative of XYZ field. The PR3-EOS and LBC correlation are applied to the UP-1 DST-3 data sets under conditions of predictions and regression. Agreement between laboratory data and regressed EOS results is generally good to excellent. The results show that that regression on critical properties of components is sufficient for good data matches. In this work, a good agreement with experimental data was obtained with grouping (lumping) 15 to 7 components.